STUDY OF PUBLIC SERVICE IMPLEMENTATION IN SOME LOCAL GOVERNMENT ORGANIZATIONS OF CENTRAL JAVA PROVINCE IN 2021 - Sodikin (Bajang Institute, 2021)
Public service is an activity or series of activities in the context of fulfilling basic needs in accordance with the civil rights of every citizen and resident of goods, services, and or administrative services provided by public service providers. The government as a public service provider is required to carry out the best service / excellent service so that the public as service users feel satisfied. The Central Java Provincial Government as a public service provider in the Central Java Province has tried to comply with the provisions of Law Number 25 of 2009 concerning Public Services, as well as in the Regulation of the Minister of Empowerment of State Apparatus and Bureaucratic Reform Number 15 of 2014 concerning Guidelines for Service Standards. Service standards at least contain: legal basis, requirements, service procedures, completion time, service costs, service products, facilities and infrastructure, competence of service providers, internal control, complaint handling, suggestions and inputs and service guarantees. However, efforts to improve public services still face several obstacles. These constraints include human resources for implementing services, inadequate service facilities and budget refocusing, causing delays in the completion of public service facilities. However, the regional apparatus organizations or technical implementing units for public service providers have been trying to come up with solutions. However, Central Java Provincial Government policies are still needed to improve the quality of services gradually